Potential applications for virtual and augmented reality technologies in sensory science. (August 2019) - Crofton, E.C.; Botinestean, C.; Fenelon, M.; Gallagher, E.
Abstract: Sensory science has advanced significantly in the past decade and is quickly evolving to become a key tool for predicting food product success in the marketplace. Increasingly, sensory data techniques are moving towards more dynamic aspects of sensory perception, taking account of the various stages of user-product interactions. Recent technological advancements in virtual reality and augmented reality have unlocked the potential for new immersive and interactive systems which could be applied as powerful tools for capturing and deciphering the complexities of human sensory perception. This paper reviews recent advancements in virtual and augmented reality technologies and identifies and explores their potential application within the field of sensory science. The paper also considers the possible benefits for the food industry as well as key challenges posed for widespread adoption. The findings indicate that these technologies have the potential to alter the research landscape in sensory science by facilitating promising innovations in five principal areas: consumption context, biometrics, food structure and texture, sensory marketing and augmenting sensory perception. Although the advent of augmented and virtual reality in sensory science offers new exciting developments, the exploitation of these technologies is in its infancy and future research will understand how they can be fully integrated with food and human responses. Industrial relevance: The need for sensory evaluation within the food industry is becoming increasingly complex as companies continuously compete for consumer product acceptance in today's highly innovative and global food environment. Recent technological developments in virtual and augmented reality offer the food industry new opportunities for generating more reliable insights into consumer sensory perceptions of food and beverages, contributing to the design and development of new products with optimised consumer benefits. These technologies also hold significant potential for improving the predictive validity of newly launched products within the marketplace. Highlights: Recent advancements in virtual and augmented reality technologies are reviewed. Emerging applications for VR and AR in sensory science are identified. Key areas in which VR and AR may prove valuable in sensory science are identified. Future research will identify how VR/AR can be integrated with food/human responses.